The THE EFFECT OF FAIRYTALE BOOK ON ORAL HYGIENE KNOWLEDGE OF SCHOOL AGE CHILDREN GRADE 2 AT SDN 1 JALMPRANG WONOSOBO REGENCY - NADILA OCTAVIA PUTRI; Atika Dhiah Anggraeni (Jurnal Ilmu Keperawatan Anak, 2022)
Oral hygiene in children is still considered an epidemic concern in today's society. Early prevention can reduce the morbidity of oral hygiene problems such as dental caries which most often occurs in children. In particular, anapproach to health promotion through various media is needed to overcome this problem. One of which is suitable to be given to children is the media of fairy tales. It is in accordance with the characteristics of imaginative children. The purpose of this study was to determine the effect of fairy tale book media on the oral hygiene knowledge of school-age children. The research employed a quantitative method with a quasi-experimental one-group pretest-posttest design. The results of this study indicate that the media of fairy tales has an effect on increasing knowledge of oral hygiene in school-age children. Keywords: , Fairy Tale Books, Knowledge, Oral Hygiene, School-Age Children.